Homegoing - Gyasi, Yaa (London Penguin Books, 2017)
Effia and Esi: two sisters with two very different destinies. One sold into slavery; one a slave trader's wife. The consequences of their fate reverberate through the generations that follow. Taking us from the Gold Coast of Africa to the cotton-picking plantations of Mississippi; from the missionary schools of Ghana to the dive bars of Harlem, spanning three continents and seven generations, Yaa Gyasi has written a miraculous novel - the intimate, gripping story of a brilliantly vivid cast of characters and through their lives the very story of America itself
Keywords: Ghana -- Slavery -- Women